ΔNp63α promotes Epstein-Barr virus latency in undifferentiated epithelial cells. - Nicholas Van Sciver; Makoto Ohashi; Dhananjay M Nawandar; Nicholas P Pauly; Denis Lee; Kathleen R Makielski; Jillian A Bristol; Sai Wah Tsao; Paul F Lambert; Eric C Johannsen; Shannon C Kenney (PLoS Pathogens, 2021)
Epstein-Barr virus (EBV) is a human herpesvirus that causes infectious mononucleosis and contributes to both B-cell and epithelial-cell malignancies. EBV-infected epithelial cell tumors, including nasopharyngeal carcinoma (NPC), are largely composed of latently infected cells, but the mechanism(s) maintaining viral latency are poorly understood. Expression of the EBV BZLF1 (Z) and BRLF1 (R) encoded immediate-early (IE) proteins induces lytic infection, and these IE proteins activate each other's promoters. ΔNp63α (a p53 family member) is required for proliferation and survival of basal epithelial cells and is over-expressed in NPC tumors. Here we show that ΔNp63α promotes EBV latency by inhibiting activation of the BZLF1 IE promoter (Zp). Furthermore, we find that another p63 gene splice variant, TAp63α, which is expressed in some Burkitt and diffuse large B cell lymphomas, also represses EBV lytic reactivation. We demonstrate that ΔNp63α inhibits the Z promoter indirectly by preventing the ability of other transcription factors, including the viral IE R protein and the cellular KLF4 protein, to activate Zp. Mechanistically, we show that ΔNp63α promotes viral latency in undifferentiated epithelial cells both by enhancing expression of a known Zp repressor protein, c-myc, and by decreasing cellular p38 kinase activity. Furthermore, we find that the ability of cis-platinum chemotherapy to degrade ΔNp63α contributes to the lytic-inducing effect of this agent in EBV-infected epithelial cells. Together these findings demonstrate that the loss of ΔNp63α expression, in conjunction with enhanced expression of differentiation-dependent transcription factors such as BLIMP1 and KLF4, induces lytic EBV reactivation during normal epithelial cell differentiation. Conversely, expression of ΔNp63α in undifferentiated nasopharyngeal carcinoma cells and TAp63α in Burkitt lymphoma promotes EBV latency in these malignancies.